1995
DOI: 10.1111/j.1365-2672.1995.tb03173.x
|View full text |Cite
|
Sign up to set email alerts
|

Random amplified polymorphic DNA and restriction enzyme analysis of PCR amplified rDNA in taxonomy: two identification techniques for food‐borne yeasts

Abstract: The random amplified polymorphic DNA (RAPD) assay and the restriction enzyme analysis of PCR amplified rDNA are compared for the identification of the common spoilage yeasts Zygosaccharomyces bailii, Z. rouxii, Saccharomyces cerevisiae, Candida valida and C. lipolytica. Both techniques proved to be adequate tools for yeast identification. Since the RAPD does provide less stable patterns than restriction enzyme analysis of PCR amplified rDNA, and a large amount of data had to be compared without data reduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Furthermore, using these three primers in combination con®rms the relatedness ®ndings, because the oligonucleotides randomly target regions of the genome and the use of multiple primers leads to diversi®cation of the zones ampli®ed. Moreover, RAPD tells us about the phylogenetic links between strains (Baleiras Couto et al 1995). The strains of the species G. fragrans and G. capitatum show only 20% homology with the strains of G. candidum.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using these three primers in combination con®rms the relatedness ®ndings, because the oligonucleotides randomly target regions of the genome and the use of multiple primers leads to diversi®cation of the zones ampli®ed. Moreover, RAPD tells us about the phylogenetic links between strains (Baleiras Couto et al 1995). The strains of the species G. fragrans and G. capitatum show only 20% homology with the strains of G. candidum.…”
Section: Discussionmentioning
confidence: 99%
“…The complete NTS region was amplified with the primers NTS F and nts R (Gibco Brl). The sequence of the primers were: 5¢-TGA ACG CCT CTA AGY CAG AAT C for NTS F and 5¢-TTA TAC TTA GAC ATG CAT GGC for NTS R. Final concentrations in the PCR mixture were described by Baleiras Couto et al 1995. The PCR program utilized was as follows: 5 min at 94°C, followed by 30 cycles of 30 s at 94°C, 1 min at 57°C and 3 min at 72°C; then the mixture was heated at 72°C for 2 min and subsequently cooled at 4°C.…”
Section: Amplification and Restriction Analysis Of Nts Regionmentioning
confidence: 99%
“…Over the last decade molecular techniques for the identification and typing of micro-organisms have been widely studied. Thus, the applicability of molecular techniques, such as the RAPD method (Baleiras Couto et al 1994) and restriction enzyme analysis of PCR-amplified small subunits (Baleiras Couto et al 1995) have been demonstrated as a tool for taxonomic purposes providing information on the species level.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the first applications of PCA and cluster analysis to the study of DNA and RNA fragments of several biological systems in the field of microbiology were done by Couto et al (1995), Johansson et al (1995) and Boon et al (2002). The study by Boon et al (2002) reported the diversity of bacterial groups of activated sludge samples that received waste water from four different types of industry by PCR-DGGE.…”
Section: Microbiologymentioning
confidence: 99%